2018
DOI: 10.15671/hjbc.2018.218
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma citrinoviride: A Potent Biopriming Agent for the Alleviation of Salt Stress in Maize

Abstract: K üresel nüfus artışı ve endüstriyel kirlilik, tuz stresi ile birleştiğinde, tarımsal şartları ağırlaştıran çevresel tehditlere dönüşmektedir. Yeni fungal izolatların moleküler karakterizasyonu ve bunların tarım üzerindeki etkilerinin araştırılması, tuz stresi toleransının kontrolünde çevre dostu bir yaklaşım olabilir. Bu bağlamda mevcut çalışmada, doza bağımlı tuz (NaCl) stresi uygulanan mısır tohumlarına fungal ön muamele gerçekleştirilmiştir. Fungusun genetik bağlantıları iyi bilinen ITS barkodları kullanıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(36 reference statements)
4
4
0
Order By: Relevance
“…In the present study, T. citrinoviride increased the leaf dry weight of strawberry plants. Our results corroborated with the findings of Yesilyurt et al [27] who reported that T. citrinoviride alleviates the adverse effects of salt stress in maize growth. In previous study, ameliorative effect of T. citrinoviride on maize growth under salt stress was attributed to the efficient role of Trichoderma in photosynthesis mechanism and osmolyte accumulation which is known to promote plant growth [27].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, T. citrinoviride increased the leaf dry weight of strawberry plants. Our results corroborated with the findings of Yesilyurt et al [27] who reported that T. citrinoviride alleviates the adverse effects of salt stress in maize growth. In previous study, ameliorative effect of T. citrinoviride on maize growth under salt stress was attributed to the efficient role of Trichoderma in photosynthesis mechanism and osmolyte accumulation which is known to promote plant growth [27].…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborated with the findings of Yesilyurt et al [27] who reported that T. citrinoviride alleviates the adverse effects of salt stress in maize growth. In previous study, ameliorative effect of T. citrinoviride on maize growth under salt stress was attributed to the efficient role of Trichoderma in photosynthesis mechanism and osmolyte accumulation which is known to promote plant growth [27]. Another possible reason for improved plant growth by Trichoderma might be due to decreased ROS induced-oxidative damage in stressed plants that was also evident by lower lipid peroxidation levels.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations